Whole body MRI (WB-MRI) assessment of metastatic spread in prostate cancer: Therapeutic perspectives on targeted management of oligometastatic disease - Larbi, Ahmed; Dallaudière, Benjamin; Pasoglou, Vasiliki; Padhani, Anwar; Michoux, Nicolas; Vande Berg, Bruno C.; Tombal, Bertrand; Lecouvet, Frédéric E. (The Prostate, 2016)
OBJECTIVES To determine the proportion of prostate cancer (PCa) patients with oligometastatic disease (≤3 synchronous lesions) using whole body magnetic resonance imaging with diffusion‐weighted imaging (WB‐MRI/DWI). To determine the proportion of patients with nodal disease confined within currently accepted target areas for extended lymph node dissection (eLND) and pelvic external beam radiation therapy (EBRT). SUBJECTS AND METHODS Two radiologists reviewed WB‐MRI/DWI studies in 96 consecutive newly diagnosed metastatic PCa patients; 46 patients with newly diagnosed castration naive PCa (mHNPC) and 50 patients with first appearance of metastasis during monitoring for non‐metastatic castration resistant PCa (M0 to mCRPC). The distribution of metastatic deposits was assessed and the proportions of patients with oligometastatic disease and with LN metastases located within eLND and EBRT targets were determined. RESULTS Twenty‐eight percent of mHNPC and 50% of mCPRC entered the metastatic disease with ≤3 sites. Bone metastases (BM) were identified in 68.8% patients; 71.7% of mHNPC and 66% mCRPC patients. Most commonly involved areas were iliac bones and lumbar spine. Enlarged lymph nodes (LN) were detected in 68.7% of patients; 69.6% of mHNPC and 68.0% of mCRPC. Most commonly involved areas were para‐aortic, inter‐aortico‐cava, and external iliac areas. BM and LN were detected concomitantly in 41% of mHNPC and 34% of mCRPC. Visceral metastases were detected in 6.7%. Metastatic disease was confined to LN located within the accepted boundaries of eLND or pelvic EBRT target areas in only ≤25% and ≤30% of patients, respectively. CONCLUSIONS Non‐invasive mapping of metastatic landing sites in PCa using WB‐MRI/DWI shows that 28% of the mHNPC patients, and 52% of the mCRPC can be classified as oligometastatic, thus challenging the concept of metastatic targeted therapy. More than two thirds of metastatic patients have LN located outside the usually recommended targets of eLND and pelvic EBRT. Prophylactic or salvage treatments of these sole areas in patients with high‐risk prostate cancer may not prevent the emergence of subsequent metastases. Prostate 76:1024–1033, 2016. © 2016 Wiley Periodicals, Inc.